Quinoline containing chalcone derivatives as cholinesterase inhibitors and their in silico modeling studies. (October 2018) - Shah, Muhammad Shakil; Najam-ul-Haq, Muhammad; Shah, Hamid Saeed; Farooq Rizvi, Syed Umar; Iqbal, Jamshed
Graphical abstract: Highlights: Quinoline chalcone derivatives were screened for cholinesterase inhibition profile. Compounds exhibited inhibition against BChE to a considerable extent. Molecular docking studies were also carried out for potent and selective inhibitors of AChE and BChE. Drug likeness of tested molecules were carried out by in-silico ADME evaluation. Abstract: Cholinesterases (ChEs) play a vital role in regulating cholinergic transmission. Inhibition of ChEs is thought to be an emerging and useful therapeutic target for neurodegenerative disorders through restoration of acetylcholine (ACh) levels in the brain ( e.g . Alzheimer's disease). To increase the chemical diversity of cholinesterase inhibitors, a series of quinoline chalcones derivatives were tested against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) isoenzymes. All tested compounds (4a-1; 5a-s) exhibited inhibitory activities against AChE and BChE to a considerable extent. Molecular docking studies were performed by using homology models on both AChE and BChE isoenzymes with the aim of exploring probable binding modes of the most potent inhibitor. In order to evaluate drug likeness of newly tested molecules, we carried out in-silico ADME evaluation. All compounds displayed favourable ADME findings which predict good oral bioavailability of these derivatives. Due to an excellent ADME profile the tested compounds were predicted to be safer which can be considered as novel cholinesterase inhibitors.